Veterinarians' perspective on telemedicine in Germany - Becker, Björn; Tipold, Andrea; Ehlers, Jan; Kleinsorgen, Christin (Frontiers in Veterinary Science, 2023)
Information on the use of telemedical approaches in the context of veterinary medicine is evolving. As in human medicine, veterinary medicine is subject to an increasing digitalisation effort. The aim of the current study was to investigate the perspective of German veterinarians regarding their awareness and usage of telemedical approaches. Furthermore, the degree of implementation of different digital approaches in the context of German veterinary medicine was elaborated. A literature review, that also aimed to address the necessary framework or standardisation of these digitalisation efforts and potential barriers such as legal or infrastructural aspects, provided information for empirical research. Using a quantitative research approach, the perspective of German veterinarians was surveyed. In total, responses from 169 veterinarians were analysed. The results show that digital approaches were used by veterinarians and the usage was enhanced by the COVID-19 crisis. However, the lack of a clear legal framework may be a significant barrier for further implementation. This survey provides a basis for a critical discussion on the use of veterinary telemedicine in Germany. The results may contribute to future strategies for the implementation and development of necessary policies, training and service applications within Germany, which may be transferable for the profession in other countries.